Penerapan Branding Produk Dan Digital Marketing Dalam Meningkatkan Omset Penjualan Pada Kedai Viaipi Kabupaten Jombang - Bekti Widyaningsih; Arivatu Ni’matika Rahmatika; Milla Ahmada (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research is motivated by the increasingly fierce competition in the coffee shop industry, so that the application of product branding and digital marketing is an important factor in increasing sales turnover, especially in micro, small and medium enterprises such as Kedai Viaipi in Jombang Regency. This study aims to analyze the role of branding and digital marketing strategies in driving the growth of the coffee shop business. The method used is descriptive qualitative with data collection through observation, interviews, and documentation studies. The results showed that the consistent application of branding through visual elements, packaging, and attractive interior concepts succeeded in building brand identity and increasing customer loyalty, especially among young people. On the other hand, the utilization of social media such as Instagram, TikTok, and Facebook with creative content, influencer collaboration, and interactive promotions proved effective in expanding market reach and increasing customer engagement. The positive impact of the integration of these two strategies is reflected in a 30% increase in sales turnover in the last six months and an increase in the number of customers from various regions. Obstacles faced, such as competition on social media and limited resources, can be overcome through innovation, employee training, and good supplier management. The study concludes that a combination of product branding and digital marketing is the key to success.